Review of Acute Kidney Injury Classification Using Machine Learning - Shah N.N.H.; Razak N.; Abu-Samah A.; Razak A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Adaptive boosting; Biomedical engineering; Decision trees; Forecasting; Intensive care units; Nearest neighbor search; Sensitivity analysis; Support vector machines; Complementary data; Gradient boosting; Insulin sensitivity; K-nearest neighbours; Kidney function; Machine learning techniques; Performance based; Receiver operating characteristic curves; Learning systems